Prothrombin complex concentrate in cardiac surgery: A systematic review and meta-analysis - Roman M; Biancari F; Ahmed AB; Agarwal S; Hadjinikolaou L; Al-Sarraf A; Tsang G; Oo AY; Field M; Santini F; Mariscalco G (My University, 2022)
Prothrombin complex concentrate (PCC) has recently emerged as effective alternative to fresh frozen plasma (FFP) in treating excessive perioperative bleeding. We performed a systematic review and meta-analysis to evaluate the safety and efficacy of PCC administration as first-line treatment for coagulopathy following adult cardiac surgery.\nWe searched PubMed/MEDLINE, EMBASE, and the Cochrane Library from inception to the end of March 2018 to identify eligible articles. Adult patients undergoing cardiac surgery and receiving perioperative PCC were compared to those receiving FFP.\nA total of 861 adult patients from 4 studies were retrieved. No randomized studies were identified. Pooled odds ratio (OR) showed that PCC cohort was associated with a significant reduction in the risk of RBC transfusion (OR: 2.22; 95% confidence interval [CI] 1.45-3.40) and units of RBC received (OR: 1.34; 95%CI: 0.78-1.90). No differences were observed between the groups for re-exploration for bleeding (OR: 1.09; 95%CI: 0.66-1.82), chest drain output at 24 hours (OR: 66.36; 95%CI: -82.40-216.11), hospital mortality (OR: 0.94; 95%CI: 0.59-1.49), stroke (OR: 0.80; 95%CI: 0.41-1.56), and occurrence of acute kidney injury (OR: 0.80; 95%CI: 0.58-1.12). A trend toward increased risk of renal replacement therapy was observed in the PCC group (OR: 0.41; 95%CI: 0.16-1.02).\nIn patients with significant bleeding following cardiac surgery, PCC administration seems to be more effective than FFP in reducing perioperative blood transfusions. No additional risks of thromboembolic events or other adverse reactions were observed. Randomized controlled trials are needed to definitively establish the safety of PCC in cardiac surgery.